A Study of Applications of E-Commerce - Yadav, D. R; Sharma, Reena (Journal of Commerce and Trade, 2011)
There are wide varieties of e-commerce application areas that have flourished over the last decade in more detail, it is worth looking at one which may not be familiar to a reader, but which saves companies huge amounts of resources. The application involves a supply chain. A supply chain is a set of relationships between a number of companies who have a symbiotic relationship with each other in that one company supplies commodities or services to other companies which, in turn, supply commodities or services to other companies, and so on. The example was originally described by Kalakota and Robinson (1999) in their excellent management introduction to e-commerce. It concerns the processes involved in getting a bottle of Listerine mouthwash to the shelves of a retail chemist.